Mengurai Kebermaknaan Sosok Ibu dalam Buku “Bu Aku Ingin Pelukmu” karya Reza Mustopa dan Relevansinya terhadap Adab kepada Orangtua - Huda, Ali Anhar Syi’bul; Aghnia, Aghnia; Nurhuda, Abid; Ahmad, Walid In’am; Hamdi, Hamdi; Anugrah, Dena Sri (PT PUBLIKASI INSPIRASI INDONESIA, 2026)
This study is motivated by the importance of understanding the meaningful role of mothers in children’s lives and the declining awareness of filial piety in modern society. The research aims to analyze the representation of mothers, the underlying values, moral messages, their relevance to the concept of filial piety (birrul walidain) in Islamic education, and the contribution of the book “Bu Aku Ingin Pelukmu” by Reza Mustopa. This study employs a qualitative approach using a literature study method. Data were collected through textual analysis of the book as the primary source, supported by relevant scholarly literature, and analyzed using descriptive qualitative techniques involving data reduction, presentation, and conclusion drawing. The findings reveal five main points: (1) the mother is represented as a figure of unconditional love, a source of strength, and a place of return; (2) the values include love, resilience, self-reflection, and spirituality; (3) moral messages emphasize the importance of respecting and honoring mothers; (4) these values align with the concept of filial piety in Islamic education; and (5) the book contributes as an educational medium in fostering awareness of respecting parents. This study recommends interdisciplinary expansion in law, sociology, and value and character education, along with practical implementation through literacy programs and contextual learning in schools and families.